 2.1. ORDER THEORY

17

Proposition

69

.

If

b

is complementive to

a

then (

a

\

b

)

t

b

=

a

.

Proof.

Because

b

v

a

by the previous proposition.

Definition

70

.

Let

A

be a bounded distributive lattice. The

complement

(denoted ¯

a

) of an element

a

A

is such

b

A

that

a

u

b

=

and

a

t

b

=

>

.

Proposition

71

.

If

A

is a bounded distributive lattice then ¯

a

=

> \

a

.

Proof.

b

= ¯

a

b

u

a

=

⊥∧

b

t

a

=

> ⇔

b

u

a

=

⊥∧>t

a

=

a

t

b

b

=

>\

a

.

Corollary

72

.

If

A

is a bounded distributive lattice then exists no more than

one complement of an element

a

A

.

Definition

73

.

An element of bounded distributive lattice is called

comple-

mented

when its complement exists.

Definition

74

.

A distributive lattice is a

complemented lattice

iff every its

element is complemented.

Proposition

75

.

For a distributive lattice (

a

\

b

)

\

c

=

a

\

(

b

t

c

) if

a

\

b

and

(

a

\

b

)

\

c

are defined.

Proof.

((

a

\

b

)

\

c

)

u

c

=

; ((

a

\

b

)

\

c

)

t

c

= (

a

\

b

)

t

c

; (

a

\

b

)

u

b

=

;

(

a

\

b

)

t

b

=

a

t

b

.

We need to prove ((

a

\

b

)

\

c

)

u

(

b

t

c

) =

and ((

a

\

b

)

\

c

)

t

(

b

t

c

) =

a

t

(

b

t

c

).

In fact,

((

a

\

b

)

\

c

)

u

(

b

t

c

) =

(((

a

\

b

)

\

c

)

u

b

)

t

(((

a

\

b

)

\

c

)

u

c

) =

(((

a

\

b

)

\

c

)

u

b

)

t ⊥

=

((

a

\

b

)

\

c

)

u

b

v

(

a

\

b

)

u

b

=

,

so ((

a

\

b

)

\

c

)

u

(

b

t

c

) =

;

((

a

\

b

)

\

c

)

t

(

b

t

c

) =

(((

a

\

b

)

\

c

)

t

c

)

t

b

=

(

a

\

b

)

t

c

t

b

=

((

a

\

b

)

t

b

)

t

c

=

a

t

b

t

c.

2.1.8. Boolean lattices.

Definition

76

.

A

boolean lattice

is a complemented distributive lattice.

The most important example of a boolean lattice is

P

A

where

A

is a set,

ordered by set inclusion.

Theorem

77

.

(De Morgan’s laws) For every elements

a

,

b

of a boolean lattice

1

.

a

t

b

= ¯

a

u

¯

b

;

2

.

a

u

b

= ¯

a

t

b

.

Proof.

We will prove only the first as the second is dual.

It is enough to prove that

a

t

b

is a complement of ¯

a

u

¯

b

. Really:

(

a

t

b

)

u

a

u

¯

b

)

v

a

u

a

u

¯

b

) = (

a

u

¯

a

)

u

¯

b

=

⊥ u

¯

b

=

;

(

a

t

b

)

t

a

u

¯

b

) = ((

a

t

b

)

t

¯

a

)

u

((

a

t

b

)

t

¯

b

)

w

(

a

t

¯

a

)

u

(

b

t

¯

b

) =

> u >

=

>

.

Thus (

a

t

b

)

u

a

u

¯

b

) =

and (

a

t

b

)

t

a

u

¯

b

) =

>

.